STATISTICAL ANALYSIS ON THE EFFECT OF REMOVABLE PARTIAL DENTURES ON THE PERIODONTIUM - Carmen Silvano; Sorana Maria Bucur; Dorin Ioan Cocoș; Alexandru Vlasa (Romanian Society of Oral Rehabilitation, 2022)
Aim of the study: To evaluate the factors which contribute to periodontal damage in cases of patients with removable partial dentures. Material and method: a questionnaire was created using the Google Forms platform, and it was addressed to 140 dentists of all ages. The data was processed and analyzed statistically and descriptively using the Microsoft Excel module in the Microsoft Office 2013 programming package. Results: Poor oral hygiene is considered one of the most common risk factors associated with periodontal tissue damage Gingival recessions have been identified in most of the cases. Dentists who answered the questionnaire didn't consider that bone resorption was accelerated by removable partial dentures wear. The dentists preferred to use cast clasps in removable partial dentures. Conclusion: It is important to take into account and preserve the patient's periodontal health when manufacturing a removable partial denture.